Expression and Purification of HPF Protein from Staphylococcus aureus and Analysis of Its Structure by the Method of NMR Spectroscopy - R.Kh. Ayupov; K.S. Usachev; I.Sh. Khusainov; B. Kieffer; M.M. Yusupov (Учёные записки Казанского университета: Серия Естественные науки)
Staphylococcus aureus hibernation-promoting factor (SaHPF) is a 22.2 kDa translation factor which under stress conditions (under amino acid starvation or antibiotic pressure) binds with the ribosome and inactivates it, thereby ensuring cell survival under stress. There are many problems with crystallization of this protein which still remain unsolved. Therefore, its analysis by NMR spectroscopy is of great interest. In this paper, we have described expression, purification, and NMR analysis of 13C/15N-labeled SaHPF protein and showed that it is present in a dimeric form in the solution. Notably, two types of signals in the NMR spectra have been observed: with weak intensity and high dispersion from N-terminal domain; with high intensity but low dispersion from a flexible loop between domains. No signals from C-terminal domain have been observed in the NMR spectra, which may indicate possible dimerization of this part of the protein. Protein dimerization has been also detected by the method of electrophoresis under native conditions.